Hubungan Tympanogram dengan Lokasi dan Ukuran Tumor pada Pasien Karsinoma Nasofaring - Dewi, Julita Melisa; Marliyawati, Dwi; Muyassaraoh, Muyassaroh (Medica Hospitalia : Journal of Clinical Medicine, 2022)
Introduction : Hearing loss is the most frequent symptomps of patients with Nasopharyngeal Carcinoma (NPC), because there is a connection between the middle ear and the nasopharynx through the eustachian tube. Tympanometry is a hearing test in terms of evaluating the middle ear. Objective : This study aimed to evaluate the correlation between the tympanogram and the location and size of the nasopharyngeal carcinoma tumor at Dr. Kariadi General Hospital Semarang. Methods : This is a descriptive analytic study with cross-sectional study design of NPC patients at Dr. Kariadi Hospital Semarang, July 2020 to June 2021. Tympanometry was performed at the beginning of the diagnosis of NPC, the location and size of the tumor based on a head and neck physical examination, nasopharyngoscopy and CT scan results. Data analysis with spearmen rho . test. Result : From 52 subjects were diagnosed with NPC, most of them were in the 5th decade. The most common location of the tumor was in Rossenmuler fossa and extended to the wall and roof of the nasopharynx bilaterally (n=29; 55,7%). The most tumor size was T4 (n=26;50%). The results of statistical analysis showed that the tympanogram image had a strong correlation with the location of the tumor in NPC patients (r=0.853; p<0.001), but had no correlation with tumor size (r=0.061; p=0.668). Conclusion : The tympanogram in NPC is related to the location of the tumor, not to the size of the tumor.